2022
DOI: 10.3390/ma15113915
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Testing Designs for Flexural Strength of 3Y-TZP and 5Y-PSZ Considering Different Surface Treatment

Abstract: The aim of this study was to analyze the influence of different surface treatments and the corresponding surface roughness on the ball-on-three-balls test and piston-on-three-balls test for measuring flexural strength 3Y-TZP and 5Y-PSZ. Additionally, the influence of cutting the material into the specimens when pre-sintered or fully sintered was analyzed. A total of 120 specimens for each material group, 3Y-TZP zirconia (Katana HT, Kuraray) and the 4 different layers of multilayered 5Y-PSZ zirconia (Katana UTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a previous study, air particle abrasion did not significantly decrease the fracture resistance of 5Y-Z crowns cemented with RMGIC [18]. These results are in contrast with studies which report that air particle abrasion reduces the strength of 5Y-Z discs [22,25,26]. As air particle abrasion has not been shown to impact the bond strength with RMGIC, it is at the clinicians' and laboratories' discretion if 5Y-Z crowns are routinely air particle-abraded [27].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a previous study, air particle abrasion did not significantly decrease the fracture resistance of 5Y-Z crowns cemented with RMGIC [18]. These results are in contrast with studies which report that air particle abrasion reduces the strength of 5Y-Z discs [22,25,26]. As air particle abrasion has not been shown to impact the bond strength with RMGIC, it is at the clinicians' and laboratories' discretion if 5Y-Z crowns are routinely air particle-abraded [27].…”
Section: Discussionmentioning
confidence: 77%
“…Without air particle abrasion, the bond strength to both 3Y-Z and 5Y-Z decreases significantly [22][23][24]. The flexural strength of 3Y-Z is not negatively affected by air particle abrasion; however, 5Y-Z can be weakened following air particle abrasion [22,25,26]. With the use of RMGIC on zirconia crowns, air particle abrasion has not been shown to improve the bond as it has with resin cement [27].…”
Section: Introductionmentioning
confidence: 99%
“…Our present findings are supported by those of other authors; however, previous studies have mainly evaluated Ra surface roughness. Nevertheless, they proved that the 3Y-TZP surface roughness increased with the size of alumina particles used for air abrasion and confirmed a significant increase when compared to untreated specimens [23,26,33,35,39,40,47,48].…”
Section: Discussionmentioning
confidence: 94%
“…As a result, it is suggested that sandblasting particles of 110 µm be employed for 3Y-TZP, while 50 µm particles are recommended for 4Y-PSZ and 5Y-PSZ. Hergeroder et al found that different surface roughness has no significant differences in flexural strength but cutting the specimens in a fully sintered state reduced flexural strength, especially in 5Y-PSZ air abrasion [61]. Investigating the outcome of different technical tools on the surface temperature and phase composition of crowns, Wertz found that burs had no influence on the phase transformation but caused a shift in preferred orientation, whereas coarse polishers induced a phase transformation to the rhombohedral phase.…”
Section: Surface Treatmentsmentioning
confidence: 99%